Stereoselective Synthesis and Cytoselective Toxicity of Monoterpene-Fused 2-Imino-1,3-thiazines - Zsolt Szakonyi; István Zupkó; Reijo Sillanpää; Ferenc Fülöp (Molecules, 2014)
Starting from pinane-, apopinane- and carane-based 1,3-amino alcohols obtained from monoterpene-based β-amino acids, a library of monoterpene-fused 2-imino-1,3-thiazines as main products and 2-thioxo-1,3-oxazines as side-products were prepared via two- or three-step syntheses. When thiourea adducts prepared from 1,3-amino alcohols and aryl isothiocyanates were reacted with CDI under mild conditions, O-imidazolylcarbonyl intermediates were isolated which could be transformed to the desired 1,3-thiazines under microwave conditions. 1,3-Thiazines and 2-thioxo-1,3-oxazine side-products could also be prepared in one-step reactions through the application of CDI and microwave irradiation. The ring-closure process was extended to cycloalkane-based γ-hydroxythioureas. The carane- and apopinane-based derivatives exhibited marked antiproliferative activity against a panel of human adherent cancer cell lines (HeLa, A2780, MCF7 and A431).